Clinical characteristics, outcomes, and costs of COVID-19 patients in Thai hospitels: a comparative analysis based on chest X-ray findings - Naruemit Sayabovorn; Pochamana Phisalprapa; Weerachai Srivanichakorn; Thanet Chaisathaphol; Chaiwat Washirasaksiri; Tullaya Sitasuwan; Chonticha Auesomwang; Chayanis Kositamongkol; Pongpol Nimitpunya; Teerapat Attachitwatin; Methee Chayakulkeeree; Pakpoom Phoompoung; et al. (BMC Infectious Diseases)
Abstract Background “Hospitels” are hotels that have been specially converted to healthcare facilities. Their utilization emerged as a resource-optimization strategy during the peak of the COVID-19 pandemic in Thailand. This study evaluated the clinical characteristics, outcomes, and admission costs of asymptomatic and mild-to-moderate COVID-19 patients treated in these facilities. Methods We conducted a retrospective analysis of adult COVID-19 patients who were admitted between July and October 2021 to two hospitels in Bangkok that were affiliated with Siriraj Hospital. Patient demographics, clinical data, vaccination status, treatment modalities, outcomes, and total costs were collected and analyzed via univariable and multivariable statistical methods. Results Of the 1729 patients, 644 (37.2%) presented with abnormal baseline chest X-rays that could imply to moderate cases. These patients were older (49.2 vs. 42.2 years, P < 0.001), had greater body weights (68.1 vs. 64.7 kg, P < 0.001) and body mass indices (26.3 vs. 24.9 kg/m2, P < 0.001), and more frequently presented comorbidities. They demonstrated an increased risk for severe COVID-19 (P < 0.001), lower full vaccination rates (P < 0.001), and higher hospital referral rates (P < 0.001). Symptomatology was largely comparable between patients with normal and abnormal baseline chest X-rays, with significant differences noted only for cough and fatigue. While the admission costs of both groups were similar, the total costs for referred patients were sixfold greater than those for discharged patients (70 545 vs. 12 010 Thai Baht, P < 0.001). Conclusions Compared with patients with normal baseline chest X-rays, COVID-19 patients with abnormal chest X-rays admitted to hospitels presented higher comorbidity rates, greater severe disease risk, and increased hospital referral rates. Referrals from the hospitels back to Siriraj Hospital substantially escalated the total costs. Vigilant monitoring of patients with initial abnormal chest X-rays in hospitels is crucial for efficient management and resource allocation.